Uso de condicionadores orgânico e inorgânico na qualidade de solo arenoso do semiárido nordestino - Primo, Bianca de Araújo (2020)
Soils in semiarid regions are naturally deficient in organic matter (OM), a condition aggravated by the predominance of sandy texture, water scarcity, and inadequate management. The addition of clay and OM as soil conditioners can promote changes in the attributes that indicate their quality by associating with mineral components and exudates from organisms. Therefore, to evaluate the effects of adding clay and OM on the quality of sandy soil in the Brazilian semiarid region, under physical, chemical and biological parameters, we carried out an experiment in a greenhouse for 75 days, testing four clay contents (10, 15, 26 and 31%), through its direct incorporation into the sandy soil and the mixture of horizons, in the absence and presence of organic compost (22.5g). The soils were characterized as to their physical, chemical, and biological attributes at the end of the experiment. For biological parameters, forage sorghum plants were used for biometric and mineral composition assessments, in addition to assessing microbial activity (RBS, CBMS, and qCO2). The results showed significant differences in microporosity and total porosity; field capacity and permanent wilt point correlated linearly with clay content and addition of compound (R2 0.99 and 0.96, respectively); soil acidity (pH, H+Al and Al3+) was significantly affected by clay content and the presence of compost; there was a decrease in EC, SB, effective and total CEC, OC, N and micronutrients. Sorghum obtained higher values of biometric attributes when adding compost and higher levels of nutrients in its absence. The microbial activity did not show significant differences in terms of clay content or the presence of compost. The principal component analysis showed a positive correlation between most of the soil physicochemical and biometric attributes of sorghum with the highest clay content. The cluster analysis correlated the treatment with a mixture of horizons and compost (26%) to the performance of the soils with the lowest clay content (10%), and the treatment with direct incorporation of clay (15%) to the soils with the highest clay content (31%). Thus, the direct incorporation of clay in the soil was more efficient than the mixture of horizons, particularly associated with the compost, presenting potential as soil conditioners in the face of natural and anthropic pressures in the semiarid.